Effect Of Short Term Administration Of Metformin On Endocrine And Clinical Parameters in Overweight/ Obese Polycystic Ovarian Syndrome (PCOS) Women - Firdous, Uzma; un Nisa Iqbal , Mehir; Ahmed Khan, Taseer (ADVANCES IN BASIC MEDICAL SCIENCES, 2023)
Objective This study was conducted to determine the effect of short term treatment of metformin on the clinical and endocrine characteristics of overweight/obese PCOS patients. Methodology This is the cohort study conducted on 180 Overweight/Obese PCOS subjects where 121 PCOS subjects were grouped as metformin (6 months) exposed and 59 PCOS subjects were grouped as metformin unexposed PCOS patients. A self-structured questionnaire was used along with blood samples for the estimation of insulin, testosterone, chemerin and omentin using Enzyme Linked Immunosorbent Assay (ELISA) while lipid profile was done using photometric methods. Results The present study found the higher prevalence of obesity, abdominal fat, weight gain, menstrual irregularities, and infertility in all PCOS patients. There were significant differences in menstrual flow, menstrual irregularities, and infertility (p < 0.05) between studied groups. Non-significant differences were observed in the clinical manifestations of PCOS (hirsutism, acne and alopecia) and other clinical parameters (p>0.05). The studied groups showed higher levels of Insulin, testosterone, chemerin, and cholesterol but the difference was found to be non-significant (p >0.05). High HDL and low LDL levels were found in the metformin exposed PCOS group (p<0.05). Moreover, a significant negative correlation between testosterone and omentin (p = 0.002) was found in the metformin unexposed PCOS group. Conclusion The present study showed that short term metformin monotherapy in overweight PCOS women does not have significant effect on BMI, insulin, testosterone and adipokines levels while significant improvement was observed in menstrual irregularities, HDL and LDL levels in the metformin exposed group. Key words: Insulin, Testosterone, Chemerin, Omentin